Observation of nodal line in non-symmorphic topological semimetal InBi - Ekahana, S; Wu, S; Jiang, J; Okawa, K; Prabhakaran, D; Hwang, C; Mo, S; Sasagawa, T; Felser, C; Yan, B; Liu, Z; Chen, Y (IOP Publishing, 2017)
Topological nodal semimetal (TNS), characterized by its touching conduction and valence bands, is a newly discovered state of quantum matter which exhibits various exotic physical phenomena. Recently, a new type of TNS called topological nodal line semimetal (TNLS) is predicted where its conduction and valence band form a degenerate one-dimension line which is further protected by its crystal symmetry. In this work, we systematically investigated the bulk and surface electronic structure of the non-symmorphic, TNLS in InBi (which is also a type II Dirac semimetal) with strong spin-orbit coupling by using angle resolved photoemission spectroscopy. By tracking the crossing points of the bulk bands at the Brillouin zone boundary, we discovered the nodal-line feature along the kz direction, in agreement with the ab initio calculations and confirmed it to be a new compound in the TNLS family. Our discovery provides a new material platform for the study of these exotic topological quantum phases and paves the way for possible future applications.